ONCOLYTIC VIRAL THERAPY IN CANCER THERAPEUTICS - Vengadaragava Chary, Krishnan; Bharatwaj, Anish (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is to provide comprehensive information of oncolytic viral therapy, from the origin to present scenario. Methods: This observational study was conducted by the Department of Pharmacology, Saveetha Medical College, Chennai between July and December 2016. Date regarding ongoing oncolytic virotherapy trials was retrieved from clinical trial database, United States and Clinical trial registry forum, India. Tamilnogene approval details were obtained from the US-Food and Drug Administration approval new drug approval information. Results: Eleven ongoing trials in Phase I and Ia are being carried out, of which 4 viral strains such as herpes, adenovirus, measles, and reovirus are used for intracerebral malignancies. Four trials have shown superior effects and seven trial results are yet to be completed. Conclusion: Oncolytic viral therapy can be as effective as targeted therapy in battling against cancer; however, long-term efficacy and safety should be established from more studies and meta-analysis.